2013
DOI: 10.7314/apjcp.2013.14.10.5805
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A Activates FasL and Induces Apoptosis Through Activation of the JNK Pathway in Human Breast Cancer Cells

Abstract: This study was conducted to analyze the molecular mechanisms responsible for anti-proliferation effects of glaucocalyxin A in cultured MCF-7 and Hs578T breast cancer cells. The concentration that reduced cell viability to 50% (IC50) after 72 h treatment was derived and potential molecular mechanisms of anti-proliferation using the IC50 were investigated as changes in cell cycle arrest and apoptosis. Gene and protein expression changes related to apoptosis were investigated by semi-quantitative RT-PCR and weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It also upregulated the expression of extrinsic apoptotic markers such as Fas and Fas ligand (FasL) at the mRNA and protein level. Moreover, the expression of p-ERK and p-JNK increased in a dose-dependent manner after glaucocalyxin A treatment [58]. Furthermore, it concentration-dependently suppressed the proliferation and induced apoptosis in human brain glioblastoma U87MG cells by activating caspase-3, while downregulating p-Akt, p-Bad, and X-linked inhibitor of apoptosis protein (XIAP) [59].…”
Section: Glaucocalyxins a And Bmentioning
confidence: 96%
“…It also upregulated the expression of extrinsic apoptotic markers such as Fas and Fas ligand (FasL) at the mRNA and protein level. Moreover, the expression of p-ERK and p-JNK increased in a dose-dependent manner after glaucocalyxin A treatment [58]. Furthermore, it concentration-dependently suppressed the proliferation and induced apoptosis in human brain glioblastoma U87MG cells by activating caspase-3, while downregulating p-Akt, p-Bad, and X-linked inhibitor of apoptosis protein (XIAP) [59].…”
Section: Glaucocalyxins a And Bmentioning
confidence: 96%
“…Pharmacological studies have identified the bioactivities of Wangzaozins. For example, glaucocalyxin A has been widely studied for certain important biological activities, including antitumor [ 11 ], apoptosis induction [ 12 , 13 ], antibacterial, anti-oxidative, anticoagulative, antithrombotic, antifibrotic, immune, and antineuroinflammatory activities [ 5 , 14 , 15 ]. Wangzaozin A, specifically isolated from Wang Zao Zi and not from other Isodon species, has been proved to be effective in the treatment of pneumonia, lung abscess, and pulmonary tuberculosis when applied independently.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al showed that bufalin induced growth inhibition and apoptosis in hepatocellular carcinoma cells via JNK activation [26]. Li et al also found that glaucocalyxin A induced apoptosis through activation of the JNK pathway in human breast cancer cells [27]. In accordance with these earlier reports, we found that treatment with oridonin increased the expressions of p-JNK and p-p38, but only the JNK inhibitor SP600125 could inhibit oridonin-induced activation of caspase-3 and caspase-9, demonstrating that JNK may play a major role in promoting oridonin-induced apoptosis in DLBCL.…”
Section: Discussionmentioning
confidence: 99%